Pemodelan Fuzzy Logic Control untuk Pengendali PWM pada Buck Converter - Helmy Mukti Himawan; Onny Setyawati; Hadi Suyono (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
Recently the switching mode used in a buck converter is controlled by pulse width modulation (PWM) which has relatively higher efficiency compared to a linear power supply system. In general, there are two problems that often occur in the buck converter, First, the difficulties in controlling inductor current which has considerably large ripple, and second, a transient output voltage that appears at the start-up. By using fuzzy logic control in PWM switching mode, the inductor current and output voltage of the buck converter can be controlled. Using Mamdani method fuzzy logic with 2 inputs, i.e. Error and Change of Error, the system produces 1 output, which is duty ratio. The results showed that the fuzzy logic control decreased the error of the output voltage of buck converter by 3%, and decreased the ripple in the inductor current by 1.5% up to 3%.